Fuzzy Probability and Its Applications - Dau, Mawut Daniel (Journal of Global Economy, Business and Finance, 2026)
This paper deals with a Fixed Reorder Quantity System with Backorder where the demand follows uniform distribution. The concept of fuzzy probability is applied here where the single objective stochastic inventory model is discussed and the numerical results are illustrated.